Two-choice problem of dynamic programming for infinite stage process - Bistrickas, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Бистрицкас. Бесконечношаговый дихотомический процесс решения динамического программированияV. Bistrickas. Dichotominis dinaminio programavimo sprendimo procesas su begaliniu žingsnių skaičiumi